2012
DOI: 10.7319/kogsis.2012.20.4.127
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Fire Area in Jinju City Based on Fire Mobilization Time

Abstract: This study analyzed the present status of services by fire-suppression mobilization time of fire station where is located in Jinju city, by using network analysis of GIS targeting fire station(five 119 safety centers, one 119 division) in Jinju city area. As a result, it was indicated to be 15.9% in the ratio with less than 5 minutes of mobilization time, 34.7% in the ratio with less than 8 minutes, 94% in the ratio with less than 20 minutes out of the whole fire service area in Jinju city. Even districts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…In most building fires, the suppression of the fire should be achieved within 5 to 8 minutes of the fire outbreak; otherwise, the property can be unprotected or the fire can spread to neighboring buildings [24]. Currently, the number of timber structural buildings in Japan is decreasing and an 8-minute response time has thus been implemented, replacing the previous 5-minute response time.…”
Section: Mobilization Time Criteria For Fire Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most building fires, the suppression of the fire should be achieved within 5 to 8 minutes of the fire outbreak; otherwise, the property can be unprotected or the fire can spread to neighboring buildings [24]. Currently, the number of timber structural buildings in Japan is decreasing and an 8-minute response time has thus been implemented, replacing the previous 5-minute response time.…”
Section: Mobilization Time Criteria For Fire Suppressionmentioning
confidence: 99%
“…is implementation was motivated by a fire model experiment, in which the fire growth curve demonstrated that the fire must be extinguished within 5 to 8 minutes of the outbreak. e fire growth curve has been used in computation as fundamental criteria of fire suppression mobilization in many countries including Korea, Japan, and the United Kingdom [24]. Consequently, the fire growth curve is the basic standard for the arrangement of fire station procedures.…”
Section: Mobilization Time Criteria For Fire Suppressionmentioning
confidence: 99%
“…그러나 현실적인 속력 을 반영할 경우, 15분 초과는 5,959동으로 34.4%에 달했으 며, 20분을 초과하는 발생지는 816동(4.7%)으로 분석되었다. 3.3.2 소방권역 내 출동 소방서는 원래 인구밀도와 도시의 규모 등을 고려하여 설치하게 되나, 소방권역의 경우 통상적으로 행정구역경계 의 집합으로 이루어져 있다(30) .따라서 이렇게 설정된 권역의 경우 지형지물과 도로 네 트워크 등 접근성에 대한 고찰이 결여되어 있다(8) .대형재 난이나 특별한 경우 출동구역 밖으로 출동하도록 법에서 명시하고 있다. 그러나 어디까지나 설정된 권역을 기반으 로 소방력이 운영된다는 원칙이 있어 최대의 효율을 확보 할 수 있는 권역의 조정과 소방력의 확보는 도시계획과 관 리 과정에서 논의되어야 하는 문제이다 (31) .…”
unclassified